Politeness in X Conversations with Hashtag #Pemilu2024 - Purnawati; Prihantoro; Ninuk Lustyantie (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2025)
Analyzing politeness in online discussion specifically on political election promotes valuable understanding of communication methods representing perspectives, actions, and political involvement in digital environments. This research aimed to identify the politeness strategies while discussing 2024 presidential election in Indonesia using hashtag #pemilu2024 in platform X. This research utilized both qualitative and quantitative approach. The data was taken by scraping the defined criteria using Octoparse application. After the scrapping and cleaning process, it derived as many as 307 tweets that was analyzed qualitatively by categorizing the criteria of speech act by Searle (1978) model as well as politeness strategies by Click or tap here to enter text.Brown and Levinson (1987) in Brown, (2022). Then, the data was analyzed quantitatively by calculating the percentage of each type of directiveness and politeness strategies. The findings showed that the dominant type of speech act used was Representative by 227 tweets or 74% from the total analyzed data, followed by Directive (16%), Expressive (5%), Combination (4%), Declarative (1%,) and Commissive (1 tweet, 0%). For the politeness strategy, Non-FTA (82%) was dominating the types which followed by Negative strategies (12%), Off-Record (3%), Positive strategy (2%), and the least was Bald on Record (1%). This study provides an overview of how Indonesian social media users express their political ideas in the implementation of the 2024 presidential elections which can be a reference to promote fair, informed, and participatory electoral process